The Influence of Brand Images, Social Media Marketing, Prices and Reference Groups Towards Buying Decision In Swiwings Narotama Outlet Surabaya - Monica, Septia Wahyu; Soebandhi, Santirianingrum; Wulandari, Ani (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aims to examine the influence of Brand Image, Social Media Marketing, Price And Reference Groups towards Purchasing Decision in Swiwings Narotama Outlet. Data collection techniques used was questionnaire with the analysis technique of multiple linear regression. The study found that Brand Image, Price have no significant effect towards Purchasing Decision, meanwhile Social Media and Reference Group have a significant effect towards buying decisions at Swiwings Narotama Outlet in Surabaya. Simultaneously, Brand Image, Social Media Marketing, Price and Group References have a significant effect towards Buying Decisions in Swiwings Narotama Outlet.